(untitled) (Physical Education, Health and Social Sciences, 2026)
The brown planthopper (Nilaparvata lugens Stål), a monophagous delphacid pest of rice, poses a severe threat to Basmati rice production in the Indo-Gangetic plains through direct phloem feeding, hopperburn, and transmission of viruses such as Rice Ragged Stunt Virus (RRSV) and Rice Grassy Stunt Virus (RGSV), while indirectly exacerbating Rice Tungro Virus (RTV) epidemiology. Its high fecundity, short generation time (≈30 days), wing dimorphism enabling long-distance migration, and rapid population buildup under high nitrogen and dense planting make conventional chemical control unsustainable, especially given stringent Maximum Residue Limits (MRLs) in export markets (EU, USA). This review outlines a comprehensive Integrated Pest Management (IPM) framework tailored for Basmati rice, integrating: (i) monitoring via light traps, field scouting, and Economic Threshold Levels (ETL: 3–5 hoppers/tiller); (ii) cultural practices including Alternate Wetting and Drying (AWD), balanced nitrogen management, wider spacing, alleyways, and synchronized planting; (iii) conservation of natural enemies (spiders, mirid bugs, entomopathogenic fungi like Metarhizium anisopliae and Beauveria bassiana); (iv) deployment of resistant varieties through gene pyramiding (Bph genes) and marker-assisted selection (e.g., Pusa Basmati 1847, 1885, 1886 with additional blast/BB resistance); and (v) judicious use of selective, low-residue insecticides (dinotefuran, pymetrozine, triflumezopyrim, buprofezin) only when ETLs are exceeded. Synergistic integration of these tactics reduces pesticide reliance by 50–70%, preserves ecosystem services, maintains Basmati grain quality for export, and enhances climate resilience. Challenges include migratory influxes, evolving insecticide resistance, and climate-driven outbreaks, necessitating regional surveillance, ecological engineering, and policy support for IPM adoption. This multi-tiered, ecosystem-based IPM strategy ensures sustainable, residue-compliant Basmati production while safeguarding farmer incomes and food security.